PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN STRUKTUR KEPEMILIKAN MANAJERIAL TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dani Eka Pratiwi, 13.05.52.0179; Setyowati, Widhy (Students Journal of Accounting and Banking, 2017)
The study examines the effect of the size of the company, leverage, and managerial ownership structure on the accounting conservatism. This research was conducted at the Indonesian Stock Exchange by using a go publicÂ manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2013-2015. Relationship and influence between variable is described by using multiple regression analysis The results showes that the size of the company has negative effect on accounting conservatism, Leverage has positive effect on accounting conservatism, .and managerial ownership structure had no significant effect on accounting conservatism.Keywords:Â The Size of The Company, Leverage, Managerial Ownership Structure and Accounting Conservatism